Participatory Oversight Strategy of the Lampung Provincial Election Supervisory Agency in Preventing Violations in the 2024 Elections - Ahmad Qohar; Anna Gustina Zainal; Dedy Hermawan; Nur Efendi (Journal of Research in Social Science and Humanities, 2026)
Indications of money politics, violations of civil servant neutrality, and intimidation of voters were found in various regions. This shows that participatory oversight is not yet fully optimal. Based on findings in the field, money politics is still rampant ahead of election day san. The methods are increasingly varied, such as the distribution of basic foodstuffs, digital transfers, and program promises. Many citizens still consider this to be "normal" in electoral political culture. This research was conducted in Lampung Province, which is a strategic location for studying participatory oversight practices in the implementation of elections. Lampung Province was chosen because it has a high level of political dynamics and a track record of innovation in community-based election oversight. The Lampung Province Bawaslu actively initiated various programs that directly involved the community in oversight activities, making it an interesting case study in the context of strengthening participatory democracy at the local level. Participatory Oversight in Preventing Violations through Oversight Villages, Socialization, and Complaint Centers First, Oversight Villages The implementation of participatory oversight in the Bawaslu's Oversight Village program in Lampung Province aims to build an election awareness culture at the level closest to the community, namely the village or sub-district. Second, Socialization The implementation of participatory oversight through socialization carried out by Bawaslu Lampung Province and regencies/cities focuses on efforts to build public awareness and encourage the community to play an active role in maintaining election integrity.